2022
DOI: 10.3390/nu14194203
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Diets Improve Maternal–Fetal Outcomes in CKD Pregnancies

Abstract: Reducing protein intake in patients with chronic kidney disease (CKD) limits glomerular stress induced by hyperfiltration and can prevent the progression of kidney disease; data in pregnancy are limited. The aim of this study is to analyze the results obtained in CKD patients who followed a plant-based moderately protein-restricted diet during pregnancy in comparison with a propensity-score-matched cohort of CKD pregnancies on unrestricted diets. A total of 52 CKD pregnancies followed up with a protein-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“… 110 As in CKD in general, also in pregnant women with CKD, interest has shifted from macronutrient intake to micronutrient intake and the combination of micronutrient intake by types of diet (e.g., Mediterranean diet, whole foods plant-based diet). 111 , 112 , 113 , 114 , 115 In particular, pregnancy is a well-known physiological cause of hyperfiltration in which CKD is associated with an increase in proteinuria, but this increase could be diminished by diet. 112 , 116 The Italian Study Group on Kidney and Pregnancy has performed the largest study on a plant-based, moderately protein-restricted diet in pregnant women with CKD to counterbalance this proteinuria.…”
Section: Anemia In Healthy Pregnancymentioning
confidence: 99%
See 3 more Smart Citations
“… 110 As in CKD in general, also in pregnant women with CKD, interest has shifted from macronutrient intake to micronutrient intake and the combination of micronutrient intake by types of diet (e.g., Mediterranean diet, whole foods plant-based diet). 111 , 112 , 113 , 114 , 115 In particular, pregnancy is a well-known physiological cause of hyperfiltration in which CKD is associated with an increase in proteinuria, but this increase could be diminished by diet. 112 , 116 The Italian Study Group on Kidney and Pregnancy has performed the largest study on a plant-based, moderately protein-restricted diet in pregnant women with CKD to counterbalance this proteinuria.…”
Section: Anemia In Healthy Pregnancymentioning
confidence: 99%
“… 111 , 112 , 113 , 114 , 115 In particular, pregnancy is a well-known physiological cause of hyperfiltration in which CKD is associated with an increase in proteinuria, but this increase could be diminished by diet. 112 , 116 The Italian Study Group on Kidney and Pregnancy has performed the largest study on a plant-based, moderately protein-restricted diet in pregnant women with CKD to counterbalance this proteinuria. 112 These 52 pregnant women with CKD receiving an intervention diet were compared with a propensity-score-matched cohort of CKD pregnancies on unrestricted diets.…”
Section: Anemia In Healthy Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the use of soy protein instead of animal protein, there is conflicting evidence on proteinuria [90]. Finally, Piccoli and colleagues found that pregnant CKD patients who followed a plant-based moderately protein-restricted diet had a lower increase in proteinuria from the first to the last check-up before delivery, as well as a lower risk of preterm delivery and small-for-gestational-age babies [91].…”
Section: Plant-based Diets' Effects On Proteinuriamentioning
confidence: 99%